Struktur Vegetasi di Habitat Ulin (Eusideroxylon zwageri) Cagar Alam Durian Luncuk II - Khoiriyah, Zhulfatul; Maharani, Shinta; Nopita, Melni; Sazali, Ahmad (Konservasi Hayati, 2024)
Ulin (Eusideroxylon zwageri) is a species from the family of Lauraceae. Additionally, the plant is referred to as "medang-medangan" in Indonesia. Ulin is spread across Sumatra Island and Kalimantan Island in Indonesia. Ulin is also known by another name, Ironwood (kayu besi), due to the strength of its wood. Ulin is often used as a building material, house construction, etc. This research aimed to determine the structure of plants in the Ulin habitat. The findings of this research are of considerable import as they can furnish insights into the condition of the Ulin habitat in Durian Luncuk II Nature Reserve. Moreover, the results can serve as a foundation for the Ulin management and conservation in Durian Luncuk II Nature Reserve. The method used was quantitative. The data was collected using a purposive sampling method. The data analysis was based on the Density, Dominance, Importance, and Diversity Index value. As a result, the plant diversity in the Ulin habitat consists of 26 species from 19 families, with vegetation structures comprising seedlings, saplings, poles, and trees.